Super-radiant mode in InAs—monolayer–based Bragg structures - Pozina, G. (Sci Rep, 2015)
We report direct experimental evidence of the collective super-radiant mode in Bragg structure containing 60 InAs monolayer-based quantum wells (QWs) periodically arranged in GaAs matrix. Time-resolved photoluminescence measurements reveal an appearance of the additional super-radiant mode, originated from coherent collective interaction of QWs. This mode demonstrates a super-linear dependence of the intensity and radiative decay rate on the excitation power. The super-radiant mode is not manifested in the case if only a small number of QWs is excited.